2017
DOI: 10.1007/s10519-017-9885-8
|View full text |Cite
|
Sign up to set email alerts
|

Overlap Between the General Factor of Personality and Trait Emotional Intelligence: A Genetic Correlation Study

Abstract: A previous meta-analysis (Van der Linden et al., Psychol Bull 143:36–52, 2017) showed that the General Factor of Personality (GFP) overlaps with ability as well as trait emotional intelligence (EI). The correlation between trait EI and the GFP was so high (ρ = 0.88) in that meta-analysis that these two may be considered virtually identical constructs. The present study builds on these findings by examining whether the strong phenotypic correlation between the GFP and trait EI has a genetic component. In a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
6
39
1
2
Order By: Relevance
“…But what is the nature of this relationship? Recent re-search has revealed that many of the genes that are responsible for indi-vidual differences in the Big Five are also implicated in individual differences in trait EI (Van der Linden et al, 2016;Vernon, Vanessa, Villani, Schermer, & Petrides, 2008). Psychologically, the large overlap between the GFP and trait EI stems from the fact that while personality spans a very wide remit, including attitudes intentions, and motives, its main component is emotion.…”
Section: Trait Ei and The Gfpmentioning
confidence: 99%
“…But what is the nature of this relationship? Recent re-search has revealed that many of the genes that are responsible for indi-vidual differences in the Big Five are also implicated in individual differences in trait EI (Van der Linden et al, 2016;Vernon, Vanessa, Villani, Schermer, & Petrides, 2008). Psychologically, the large overlap between the GFP and trait EI stems from the fact that while personality spans a very wide remit, including attitudes intentions, and motives, its main component is emotion.…”
Section: Trait Ei and The Gfpmentioning
confidence: 99%
“…53 In contrast, utilizing own emotions negatively predicted neuroticism because students lack of ability to manage and regulate emotions within self and others are likely to have high levels of neurotic behavior including moodiness, stressfulness, and irritability. 54 Furthermore, the results from the path analysis modeling further demonstrated that the SJTEI-AR subscales significantly predicted academic achievement. This finding supports the predictive validity of the SJTEI-AR and is consistent with the findings of several previous studies about the psychometric properties of the SJTEI .…”
Section: Discussionmentioning
confidence: 88%
“…The use of EI within this study, at least within the framework of its traditional interpretation, may be seen as a limitation, based on a new understanding of the general factor of personality (GFP). Significant evidence now exists for a degree of variability overlap between EI and the GFP that accounts for almost the entire construct (van der Linden et al, 2018). Meta-analytic evidence in particular points toward an estimate of ρ = 0.88 between EI and GFP (van der Linden et al, 2017), with further genetic studies suggesting a phenotypic correlation of r = 0.90 (van der Linden et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%
“…Significant evidence now exists for a degree of variability overlap between EI and the GFP that accounts for almost the entire construct (van der Linden et al, 2018). Meta-analytic evidence in particular points toward an estimate of ρ = 0.88 between EI and GFP (van der Linden et al, 2017), with further genetic studies suggesting a phenotypic correlation of r = 0.90 (van der Linden et al, 2018). There is some debate regarding the nature of the GFP, in respect to whether it is a substantive factor or rather it is a result of systemic statistical bias; however, the consensus seems to be that although there may be some amount of systemic bias, there remains a stable and substantive individual difference behind the GFP (van der Linden et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation